The value of a=9,b=3 and c=1
Step-by-step explanation:
The graph shown is for function f(x)
The given function is f(x)=![(\frac{1}{3}) ^{x}](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B3%7D%29%20%5E%7Bx%7D)
Table says,
X Y
-2 a
1 b
0 c
1 (1/3)
2 (1/9)
To find value of a:
From table, for output value a, input value, x=(-2)
we can write f(-2)=a
Therefore,
f(x)=![(\frac{1}{3}) ^{x}](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B3%7D%29%20%5E%7Bx%7D)
f(-2)=![(\frac{1}{3}) ^{(-2)}](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B3%7D%29%20%5E%7B%28-2%29%7D)
a=![(\frac{1}{3^{(-2)}})](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B3%5E%7B%28-2%29%7D%7D%29)
a=![3^{(2)}](https://tex.z-dn.net/?f=3%5E%7B%282%29%7D)
a=9
To find value of b:
From table, for output value a, input value, x=(-1)
we can write f(-1)=b
Therefore,
f(x)=![(\frac{1}{3}) ^{x}](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B3%7D%29%20%5E%7Bx%7D)
f(-1)=![(\frac{1}{3}) ^{(-1)}](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B3%7D%29%20%5E%7B%28-1%29%7D)
b=![(\frac{1}{3^{(-1)}})](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B3%5E%7B%28-1%29%7D%7D%29)
b=![3^{(1)}](https://tex.z-dn.net/?f=3%5E%7B%281%29%7D)
b=3
To find value of c:
From table, for output value a, input value, x=(0)
we can write f(0)=c
Therefore,
f(x)=![(\frac{1}{3}) ^{x}](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B3%7D%29%20%5E%7Bx%7D)
f(0)=![(\frac{1}{3}) ^{(0)}](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B3%7D%29%20%5E%7B%280%29%7D)
c=![(\frac{1}{3^{(0)}})](https://tex.z-dn.net/?f=%28%5Cfrac%7B1%7D%7B3%5E%7B%280%29%7D%7D%29)
c=1
Answer:
f=−px+8x−2/x
Step-by-step explanation:
its a fraction
This is exponential growth of the form
f=ir^t, f=final amount, i=initial amount, r=rate, t=time, in this case we know a=20 and r=2 so
f=20(2^t)
Answer:
= (z-y)/(a-b)
Step-by-step explanation:
ax-bx + y =z
ax-bx =z -y
x (a-b) = -y
x = (z-y) / (a-b)